Pengetahuan dan Perilaku Safety Riding Siswa SMA - Indri Wahyuningsih; Syahra Ramdana (Holistik Jurnal Kesehatan, 2021)
Knowledge and Safety Riding Behavior Among High School StudentsBackground: Young people are the most involved in traffic accidents in Indonesia, because of the risky driving style. High school students belong to one of the young age groups with an average age of 15-18 years. To ensure traffic safety, a safety riding program was established which includes disciplinary behavior in driving rules and procedures. Own behavior is influenced by factors, one of which is knowledge. Knowledge as a stimulus or stimulus and becomes the basis for action.Purpose: To find the relationship between knowledge and safety riding behavior among high school students.Method: This study used an analytical observational method with a cross sectional approach, and a simple radom sampling technique. The sample was obtained as many as 164 respondents. Then the data were analyzed using spearman rank correlation with a significance level of 5%.Results: Most of the respondents have good knowledge (67.1%), as well as behavior, the majority of respondents have safe driving behavior (82.9%). The results of the spearman rank correlation analysis showed a p-value of 0.120 or greater than a significance of 5% (p> 0.05).Conclusion: There is no significant relationship between knowledge and safety riding behavior.Keywords: Knowledge; Safety riding behavior; High school studentsPendahuluan: Kalangan usia muda merupakan yang paling banyak terlibat kasus kecelakaan lalu lintas di Indonesia, diakibatkan gaya berkendara yang beresiko. Siswa SMA termasuk salah satu kelompok usia muda dengan usia rata-rata 15-18 tahun. Untuk menjamin keselamatan lalu lintas, dibentuk program safety riding yang mencakup perilaku disiplin dalam aturan dan tatacara berkendara. Perilaku sendiri dipengaruhi faktor pembentuk salah satunya pengetahuan. Pengetahuan sebagai ransangan atau stimulus dan menjadi dasar dalam bertindak. Tujuan: penelitian ini ingin mencari hubungan pengetahuan dengan perilaku safety riding pada siswa SMA.Metode: Penelitian ini menggunakan metode observasional analitik dengan pendekatan cross sectional, dan teknik sampling simple radom sampling. Sampel diperoleh sebanyak 164 responden. Kemudian data dianalisis menggunakan korelasi spearman rank dengan tingkat kemaknaan 5%.Hasil: Sebagian besar responden memiliki pengetahuan dengan kategori baik (67,1%), begitupun dengan perilaku, mayoritas responden memiliki perilaku berkendara  aman (82,9%). Hasil analisis korelasi spearman rank didapatkan p-value 0,120 atau lebih besar dari kemaknaan 5% (p>0,05).Simpulan: Tidak terdapat hubungan signifikan antara pengetahuan dengan perilaku safety riding.